Dr. Yudiyanto, M.Si. - FENOMENA LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER (LGBT) DI INDONESIA SERTA UPAYA PENCEGAHANNYA - Yudiyanto Yudiyanto (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
Abstract The growth the actors of LGBT in Indonesia highly increases. During 2009 – 2012, it is calculated that the growth increases 37%. The increasing also follows the escalating of the access of internet, phornography, drugs and the existence of the number of LGBT communities. Despite the biological factor, the influence of close environment particularly family, friend, sexual violence, the contents of phornography and drugs are alerted as the cause of LGBT. In protecting the current case of LGBT, it needs the role of parents or familiy in the basic sex education correctly ( islami ) based on the growth common sense of the children in giving the understanding and building the sexual behaviour as the aptitude.